ANALISIS PERTIMBANGAN HAKIM TIDAK TERPENUHINYA UNSUR MEMPERKAYA DIRI DALAM PUTUSAN NOMOR 18PID.SUS-TPK2022PN SMG - Prameswari, Ajeng Trisna; Kristiyadi, Kristiyadi (Sebelas Maret University, 2022)
This research is to determine the suitability of the judge's considerations with Law no. 31 of 1999 Jo Law no. 20 of 2001 concerning the Eradication of Corruption Crimes for not fulfilling the element of self-enrichment in Decision Number 18/Pid.Sus-TPK/2022/PN SMG. This research uses normative legal research methods that are applied. This study uses a case approach or case approach. The types of legal material used include primary and secondary legal source materials, while the technique of collecting legal materials in analyzing decisions uses literature study techniques and research methods use syllogistic methods. The results of the research and discussion show that the judge's considerations are not in accordance with the provisions of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crime because the judge gives the consideration that the element of enriching oneself is not fulfilled due to the small nominal, the Judge decides with a lighter decision than a lawsuit. Meanwhile, the Defendant was proven to have increased his wealth with the proceeds of corruption so that this did not comply with the provisions of the Law on the Eradication of Criminal Acts of Corruption.Keyword: Enrich Yourself; Judge's Consideration; Corruption Crime